Mummies as medicinal tools - Rosanna Gorini (Journal of Biological Research, 2005)
The term “mummy” is thought to be derived from the Persian or Arab word “moumiya”, meaning pitch or bitumen. It likely referred to the black, hard, and resinous substance probably used by the Egyptians in their embalming procedures during the late period and Ptolemaic Roman period. During medieval times and later, Arab and European physicians thought that mummies had medicinal properties. Egyptian mummies dug out of their tombs were sometimes grinded into powder and shipped across the Mediterranean to be sold as medicine for the cure of different diseases; for example epilepsy, abscesses, rashes, migraine, nausea etc. From the 12th to the 17th centuries, mummy remains could be found in apothecaries’ shops, and as late as 1908 they could be ordered from the catalogue of the Merck pharmaceutical company.